Hubungan Nilai Pendidikan Jasmani, Motivasi Memilih Prodi PJKR Jalur PMDK, dan Hasil Tes Kesegaran Jasmani dengan Hasil Tes Keterampilan Olahraga - Siti Nurrochmah (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
This correlative study aimed at investigating the correlation between physical education grade, motivation in choosing not-test study program, and the result of physical fitness test altogether with the result of sport skill test. Using purposive sampling technique, thirty three students taken from the students of Physical Education, Health and Recreation Study Program of UM were used as samples of this study. Data were collected using documentation and questionnaire, and were analyzed by using correlation and regression technique.